Comparison of infectious complications with BCMA-directed therapies in multiple myeloma - Nath, Karthik; Shekarkhand, Tala; Nemirovsky, David; Derkach, Andriy; Costa, Bruno Almeida; Nishimura, Noriko; Farzana, Tasmin; Rueda, Colin; Chung, David J.; Landau, Heather J.; Lahoud, Oscar B.; Scordo, Michael; et al. (Blood cancer journal (New York), 2024)
B-cell-maturation-antigen (BCMA)-directed therapies are highly active for multiple myeloma, but infections are emerging as a major challenge. In this retrospective, single-center analysis we evaluated infectious complications after BCMA-targeted chimeric-antigen-receptor T-cell therapy (CAR-T), bispecific-antibodies (BsAb) and antibody-drug-conjugates (ADC). The primary endpoint was severe (grade ≥3) infection incidence. Amongst 256 patients, 92 received CAR-T, 55 BsAb and 109 ADC. The incidence of severe infections was higher with BsAb (40%) than CAR-T (26%) or ADC (8%), including grade 5 infections (7% vs 0% vs 0%, respectively). Comparing T-cell redirecting therapies, the incidence rate of severe infections was significantly lower with CAR-T compared to BsAb at 1-year (incidence-rate-ratio [IRR] = 0.43, 95%CI 0.25−0.76, P = 0.004). During periods of treatment-emergent hypogammaglobulinemia, BsAb recipients had higher infection rates (IRR:2.27, 1.31−3.98, P = 0.004) and time to severe infection (HR 2.04, 1.05–3.96, P = 0.036) than their CAR-T counterparts. During periods of non-neutropenia, CAR-T recipients had a lower risk (HR 0.44, 95%CI 0.21−0.93, P = 0.032) and incidence rate (IRR:0.32, 95% 0.17–0.59, P < 0.001) of severe infections than BsAb. In conclusion, we observed an overall higher and more persistent risk of severe infections with BsAb. Our results also suggest a higher infection risk during periods of hypogammaglobulinemia with BsAb, and with neutropenia in CAR-T recipients.